NMR relaxation in semiflexible Vicsek fractals. (23rd May 2018) - Markelov, Denis A.; Fürstenberg, Florian; Dolgushev, Maxim
Abstract: We consider the role of local orientational mobility for the NMR relaxation of hyperbranched macromolecules modeled in form of Vicsek fractals. The spectral density J ( ω ), that is relevant for the NMR relaxation, is studied for labeled segments of flexible and semiflexible Vicsek fractals. We show that the semiflexibility leads to strong effects. For flexible Vicsek fractals the function ω J ( ω ) has a single maximum, whose position is determined by the local-scale modes and therefore independent of the location of the labeled segments. For the labeled segments of a semiflexible Vicsek fractal, we observe a broad spectral density. It is characterized by the overall relaxation of the branch that originates from the labeled segment and by the overall relaxation of the subbranches that build this branch. In this way, going from the periphery to the inner part of the macromolecule, the labeled segments display a broader spectral density. However, this effect saturates when the labeled segments get closer to the core of the hyperbranched macromolecule, so that they do not feel their remoteness from the periphery anymore. Graphical abstract: Image 1 Highlights: The spectral density [ J ( ω ) ] = ω J ( ω ) involved in the NMR relaxation functions has for fractal macromolecules very strong features. For the peripheral segments [ J ( ω ) ] is characterized by a single time (like for dendrimers). For the inner segments one observes a significant broadening of [ J ( ω ) ] . The segments located deeply inside the macromolecule do not feel its size anymore (like in a network). The inclusion of local stiffness is fundamental for the NMR relaxation of branched macromolecules.